Primary hepatic mucosa-associated lymphoid tissue lymphoma: A case report and literature review. Issue 13 (March 2019) - Xie, Huazhi; Lv, Jian; Ji, Yong; Du, Xinjian; Yang, Xin
Abstract: Rationale: Primary hepatic mucosa-associated lymphoid tissue (MALT) lymphoma is a rare disease, and there is no consensus yet on the treatment modalities. Here, we report a new case of MALT lymphoma and review the current literature on this disease. Patient concerns: A 73-year-old man was admitted to our department following the incidental finding of a solitary 1.8-cm diameter mass in the liver. Diagnosis: Microscopic findings identified the mass as a tumor with infiltration of diffuse atypical B lymphocytes. Immunohistochemical analysis showed positivity for CD20 and CD79a, and negativity for CD3 and CD5. These collective data led to the diagnosis of primary hepatic MALT lymphoma. Interventions: The tumor was removed by surgical resection. The patient refused additional treatment after the surgery. Outcomes: At the time of writing this report, the patient has been disease free for 6 months postsurgery. Lessons: Review of the previously published case reports on this rare tumor type indicates that in addition to chronic liver inflammation due to infection or other reasons, genetic aberrations can also contribute to the development of hepatic MALT lymphoma. Additionally, IgH rearrangement is a good genetic hallmark of this tumor. Owing to no specific clinical or radiologic features to define the disease profile for diagnosis, surgery may be a good choice for both diagnosis and therapy if the patient's condition permits.